2020
DOI: 10.3390/cancers12040853
|View full text |Cite
|
Sign up to set email alerts
|

The Core-Clock Gene NR1D1 Impacts Cell Motility In Vitro and Invasiveness in a Zebrafish Xenograft Colon Cancer Model

Abstract: Malfunctions of circadian clock trigger abnormal cellular processes and influence tumorigenesis. Using an in vitro and in vivo xenograft model, we show that circadian clock disruption via the downregulation of the core-clock genes BMAL1, PER2, and NR1D1 impacts the circadian phenotype of MYC, WEE1, and TP53, and affects proliferation, apoptosis, and cell migration. In particular, both our in vitro and in vivo results suggest an impairment of cell motility and a reduction in micrometastasis formation upon knock… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 35 publications
1
27
1
Order By: Relevance
“…Among these genes are NR1D1 [5,18], [3,37], and PER1 [14], which participate in circadian molecular mechanism but are implicated in cancer progression as well. It is possible that suppression of these genes and activation of actins and other cell adhesion genes are done through a common Fusobacterium nucleatum-dependent regulation mechanism.…”
Section: Resultsmentioning
confidence: 99%
“…Among these genes are NR1D1 [5,18], [3,37], and PER1 [14], which participate in circadian molecular mechanism but are implicated in cancer progression as well. It is possible that suppression of these genes and activation of actins and other cell adhesion genes are done through a common Fusobacterium nucleatum-dependent regulation mechanism.…”
Section: Resultsmentioning
confidence: 99%
“…Besides the irinotecan network, the addition of a cell-cycle network could be interesting for treatment by timing medication to the cell cycle of non-cancer cells, which likely have a different clock [ 25 ]. Given the range of molecular time-dependent processes that the circadian clock regulates, including metabolism, DNA repair and the cell cycle, it has the potential to act as a tumor suppressor [ 25 , 46 ]. Indeed, several clock-controlled genes show a strong association with cancer and cancer progression, in particular genes related to metabolism [ 26 , 28 , 44 ].…”
Section: Methodsmentioning
confidence: 99%
“…In fact, studies conducted in animal models including mice [ 42 ] and the primate Papio anubis (baboon, [ 43 ]) reported that more than 80% of protein-coding genes show circadian rhythms in expression, in at least one tissue and several of these genes are involved in processes related to the so-called hallmarks of cancer [ 44 ]. These include genes governing key biological functions such as energy metabolism (e.g., NR1D1 , HKDC1 , PCK1 and GLUTs ), DNA repair (e.g., XPA and TP53 ), cell cycle (e.g., MYC , WEE1 and INK4A ), cell motility (e.g., NR1D1 and SNAI1) , as well as protein and macromolecules integrity (e.g., KRT1 , ITM2B ) [ 25 , 28 , 42 , 43 , 45 , 46 , 47 , 48 ]. The circadian clock thus plays a central role in maintaining tissue homeostasis, which, if disrupted, could lead to disease onset or progression.…”
Section: Clinical Overviewmentioning
confidence: 99%
“…This model system is further removed from mammalian biology and it is unclear if this observation is a result of the cell type or the model. Interestingly, in HCT116 BMAL1 k/d cells, p53 was shown convincingly to oscillate at the mRNA level despite no oscillation at the BMAL1 promoter (Basti et al, 2020). Studies in vitro have demonstrated BMAL1 acting as a suppressor of proliferation in BxPC-3, AsPC-1, HCT116, C26 and U87MG (glioblastoma) cell lines and in patient derived glioblastoma stem cells, but acting as a proliferation enhancer in the human MPM cell lines ACC-MESO-1 and NCI-H290 (Jiang et al, 2016, Basti et al, 2020, Gwon et al, 2020, Dong et al, 2019, Elshazley et al, 2012.…”
Section: Bmal1mentioning
confidence: 96%
“…Similarly, mutation of PER2 increased proliferation of lung cancer cells in mice, this was conserved in a p53 deficient background (Papagiannakopoulos et al, 2016). In contrast, HCT116 xenografts in zebrafish embryos showed no change upon PER2 k/d (Basti et al, 2020). Overexpression of PER2 in murine Lewis Lung Carcinoma or EMT6 (mouse mammary carcinoma) cells in vitro results in reduced proliferation and increased apoptosis (Hua et al, 2006).…”
Section: Period Genesmentioning
confidence: 98%